Screening of the active fractions from the Coreopsis tinctoria Nutt. Flower on diabetic endothelial protection and determination of the underlying mechanism. (10th May 2020) - Li, Yajuan; Huang, Chaoran; Fu, Wenwei; Zhang, Hong; Lao, Yuanzhi; Zhou, Hua; Tan, Hongsheng; Xu, Hongxi
Abstract: Ethnopharmacological relevance: The Coreopsis tinctoria Nutt. flower (CTF) has been used traditionally in China for treating hypertension and diabetes as well as reducing body weight and blood fat. However, the vascular protection effect of the CTF has not been studied to date. Aim of the study: This study aimed to screen and identify bioactive fractions from the CTF with a diabetic endothelial protection effect and to clarify the underlying mechanism. Materials and methods: The vascular protection effect of Fraction A was studied in high-fat diet and streptozocin-induced diabetic models. The endothelial protection effect of Fraction A-2 was further studied in an in vitro vascular endothelial dysfunction model induced by high glucose. In a high glucose-induced human umbilical vein endothelial cell (HUVEC) model, Fractions A-2-2 and A-2-3 were screened, and their detailed mechanisms of endothelial protection were studied. Liquid chromatography mass spectrometry (LC-MS) was used to identify the main components in Fractions A-2-2 and A-2-3. Results: Fraction A treatment significantly improved the endothelium-dependent vasodilation of the mesenteric artery induced by acetylcholine in diabetic rats. The maximum relaxation was 79.82 ± 2.45% in the control group, 64.36 ± 9.81% in the model group, and 91.87 ± 7.38% in the Fraction A treatment group ( P < 0.01). Fraction A treatment also decreased rat tail pressure compared with the model group at the 12th week. The systolic blood pressure was 152.7 5 ± 16.99 mmHg in the control group, 188.50 ± 5.94 mmHg in the model group, and 172.60 ± 14.31 mmHg in the Fraction A treatment group ( P < 0.05). The mean blood pressure was 128.50 ± 13.79 mmHg in the control group, 157.00 ± 6.06 mmHg in the model group, and 144.80 ± 11.97 mmHg in the Fraction A treatment group ( P < 0.05). In an in vitro vascular endothelium-dependent vasodilation dysfunction model induced by high glucose, Fraction A-2 improved the vasodilation of the mesenteric artery. The maximum relaxation was 82.15 ± 16.24% in the control group, 73.29 ± 14.25% in the model group, and 79.62 ± 13.89% in the Fraction A-2 treatment group ( P < 0.05). In a high glucose-induced HUVEC model, Fraction A-2-2 and Fraction A-2-3 upregulated the expression of IRS-1, Akt, and eNOS and increased the levels of p-IRS-1 Ser307, p-Akt Ser473, and p-eNOS Ser1177 and also decreased the expression of NOX4, TNF-α, IL-6, sVCAM, sICAM, and NF-κB ( P < 0.01). With the intervention of AG490 and LY294002, the above effects of Fraction A-2-2 and Fraction A-2-3 were inhibited ( P < 0.01). LC-MS data showed that in Fraction A-2-2 and Fraction A-2-3, there were 10 main components: flavanocorepsin; polyphenolic; flavanomarein; isochlorogenic acid A; dicaffeoylquinic acid; coreopsin; marein; coreopsin; luteolin-7-O-glucoside; and 3′, 5, 5', 7-tetrahydroxyflavanone-O-hexoside. Conclusion: The protective effect of the CTF on diabetic endothelial dysfunction may be due to its effect on the JAK2/IRS-1/PI3K/Akt/eNOS pathway and the related oxidative stress and inflammation. The results strongly suggested that Fraction A-2-2 and Fraction A-2-3 were the active fractions from the CTF, and the CTF might be a potential option for the prevention of vascular complications in diabetes. Graphical abstract: Image 1